background image

For such

δ

it holds (for every

X ∈

F

(

A

)

,

Y ∈

F

(

B

)

)

X

L

1

R

δ

Y ⇔ ∀

X

up

X

, Y

up

Y

:

X δ Y.

(4)

Proof

Injectivity of

L

F

and

L

R

, formulas (2) (for

α

im

L

F

) and (4) (for

δ

im

L

R

), formulas (1) and (3) follow from two previous theorems. The only

thing remained to prove is that for every

α

and

δ

that obey the above conditions

a corresponding funcoid

f

exists.

2. Let define

α

F

(

B

)

P

A

by the formula

(

αX

) =

{

Y

P

B

|

X δ Y

}

for every

X

P

A

. (It is obvious that

{

Y

P

B

|

X δ Y

}

is a free star.)

Analogously it can be defined

β

F

(

A

)

P

B

by the formula

(

βY

) =

{

X

P

A

|

X δ Y

}

.

Let’s continue

α

and

β

to

α

F

(

B

)

F

(

A

)

and

β

F

(

A

)

F

(

B

)

by the formulas

α

X

=

\

h

α

i

up

X

and

β

Y

=

\

h

β

i

up

Y

and

δ

to

δ

P

(

F

(

A

)

×

F

(

B

)) by the formula

X

δ

Y ⇔ ∀

X

up

X

, Y

up

Y

:

X δ Y.

Y ∩

α

X 6

= 0

F

(

B

)

⇔ Y ∩

T

h

α

i

up

X 6

= 0

F

(

B

)

T

hY∩i h

α

i

up

X 6

= 0

F

(

B

)

. Let’s

prove that

W

=

hY∩i h

α

i

up

X

is a generalized filter base: To prove it is enough to show that

h

α

i

up

X

is a

generalized filter base. If

A

,

B ∈ h

α

i

up

X

then exist

X

1

, X

2

up

X

such that

A

=

αX

1

and

B

=

αX

2

.

Then

α

(

X

1

X

2

)

∈ h

α

i

up

X

. So

h

α

i

up

X

is a generalized filter base and

thus

W

is a generalized filter base.

Accordingly to the corollary of the theorem 1,

T

hY∩i h

α

i

up

X 6

= 0

F

(

B

)

is

equivalent to

X

up

X

:

Y ∩

αX

6

= 0

F

(

B

)

,

what is equivalent to

X

up

X

, Y

up

Y

:

B

Y

αX

6

= 0

F

(

B

)

⇔ ∀

X

up

X

, Y

up

Y

:

Y

(

αX

)

⇔ ∀

X

up

X

, Y

up

Y

:

X δ Y

. Combining

the equivalencies we get

Y ∩

α

X 6

= 0

F

(

B

)

⇔ X

δ

Y

. Analogously

X ∩

β

Y 6

=

0

F

(

A

)

⇔ X

δ

Y

. So

Y ∩

α

X 6

= 0

F

(

B

)

⇔ X ∩

β

Y 6

= 0

F

(

A

)

, that is (

A

;

B

;

α

;

β

)

is a funcoid. From the formula

Y ∩

α

X 6

= 0

F

(

B

)

⇔ X

δ

Y

it follows that

X

[(

A

;

B

;

α

;

β

)]

Y

⇔↑

B

Y

α

A

X

6

= 0

F

(

B

)

⇔↑

A

X δ

B

Y

X δ Y.

1. Let define the relation

δ

P

(

P

A

×

P

B

) by the formula

X δ Y

⇔↑

B

Y

αX

6

= 0

F

(

B

)

.

That

¬

(

δ I

) and

¬

(

I δ

) is obvious. We have

I

J δ K

⇔↑

B

K

α

(

I

J

)

6

=

0

F

(

B

)

⇔↑

B

K

(

αI

αJ

)

6

= 0

F

(

B

)

⇔↑

B

K

αI

6

= 0

F

(

B

)

∨ ↑

B

K

αI

6

= 0

F

(

B

)

I δ K

J δ K

and

K δ I

J

⇔↑

B

(

I

J

)

αK

6

= 0

F

(

B

)

⇔ ↑

B

I

∪ ↑

B

J

αK

6

= 0

F

(

B

)

B

I

αK

∪ ↑

B

J

αK

6

= 0

F

(

B

)

⇔↑

B

I

αK

6

= 0

F

(

B

)

∨ ↑

B

J

αK

6

=

0

F

(

B

)

K δ I

K δ J

.

14